2012
DOI: 10.3109/10428194.2011.639880
|View full text |Cite
|
Sign up to set email alerts
|

Influence of folate pathway polymorphisms on high-dose methotrexate-related toxicity and survival in childhood acute lymphoblastic leukemia

Abstract: The prediction of high-dose methotrexate (HD-MTX) toxicity is a key issue in the individualization of treatment in childhood acute lymphoblastic leukemia (ALL). Our aim was to evaluate the influence of MTX pathway polymorphisms on HD-MTX treatment outcome in children with ALL. In total, 167 children with ALL were genotyped for methylenetetrahydrofolate dehydrogenase (MTHFD1) 1958G > A, methylenetetrahydrofolate reductase (MTHFR) 677C > T and 1298A > C and thymidylate synthase (TYMS) 2R > 3R polymorphisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 39 publications
3
68
3
Order By: Relevance
“…Our meta-analysis found no significant association between MTHFR A1298C polymorphism and hepatic and hematological toxicity, which is in agreement with results reported in previous studies [19,20]. The combined analysis suggested that there may be a possibly protective effect of MTHFR A1298C mutation for grade 1-4 mucositis and gastrointestinal toxicity.…”
Section: Discussionsupporting
confidence: 95%
“…Our meta-analysis found no significant association between MTHFR A1298C polymorphism and hepatic and hematological toxicity, which is in agreement with results reported in previous studies [19,20]. The combined analysis suggested that there may be a possibly protective effect of MTHFR A1298C mutation for grade 1-4 mucositis and gastrointestinal toxicity.…”
Section: Discussionsupporting
confidence: 95%
“…MTHFD1 is essential for the generation of methylene-THF required for thymidylate synthesis and MTHFD1 rs2236225 (Arg653Gln) was shown to reduce the enzyme activity33, leading to increased levels of methylene-THF and reducing cytotoxic effects of PMX 23,34. To our knowledge, no previous studies investigated the role of MTHFD1 SNPs in treatment with PMX.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of MTRR rs1801394 (Ile22Met), MTR rs1805087 (Asp919Gly), SLC19A1 rs1051266 (Arg27Cys), SLCO1B1 rs11045879 (intronic), rs4149056 (Val174Ala) and rs2900478 (intronic), ABCC2 rs717620 (5’ untranslated region (UTR) -24C>T), rs2273697 (Val417Ile) and rs2804402 (5’ UTR -1019A>G), ABCC4 rs2274407 (Lys304Asn), and ABCG2 rs2231142 (Gln141Lys) and rs2231137 (Val12Met) polymorphisms was carried out using a fluorescence-based competitive allele-specific (KASPar) assay according to the manufacturer’s instructions (KBiosciences, Herts, UK). Determination of promoter TYMS rs34743033 (5’ UTR 2R>3R) polymorphism23 and ABCB1 rs2032582 (Ala893Ser/Thr) polymorphism was carried out using PCR amplification followed by the analysis of PCR fragments on agarose gel as previously described 24…”
Section: Methodsmentioning
confidence: 99%
“…MTHFR polymorphisms were also interactions with other polymorphisms, such as RFC, 19-bp deletion, and TS. Erčulj et al [57] found that MTHFD1 A1958G and MTHFR C677T polymorphisms had an antagonistic effect interaction on hepatotoxicity [SF=0.02, 95 %CI=0.00-0.58, P=0.022]. Other authors were also analyzed by the gene-gene interactions between MTHFR and other polymorphisms which have referred in the former sections [53,57,58].…”
Section: Methylenetetrahydrofolate Reductasementioning
confidence: 97%